PENGARUH NET PROFIT MARGIN, LEVERAGE DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS (PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI - Carmenita, Tamara; Armeliza, Diah; Utaminingtyas, Tri Hesti (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
The purpose of this research is to investigate the relationship between financial distress and net profit margin, leverage, and sales growth. The population of this study consists of companies in the real estate and property sectors that will be listed on the Indonesia Stock Exchange in 2020–2022. 150 samples total were used in this study. Purposive sampling was employed during the sample procedure. Data sources are secondary data, and the study method is quantitative. With EViews version 12, panel data regression analysis is used as the data analysis technique. The findings of this study offer empirical proof that financial distress can be affected by the variables of net profit margin and leverage. but a decline in sales has no effect on financial difficulty